Predicting injuries in elite female football players with global positioning system and multiomics data - González, J. R.; Cáceres, A.; Ferrer, E.; Balagué-Dobón, L.; Escribà-Montagut, X.; Sarrat-González, D.; Quintás, G.; Rodas, G. (International Journal of Sports Physiology and Performance, 2024)
Purpose Injury prevention is a crucial aspect of sports, particularly in high-performance settings such as elite female football. This study aimed to develop an injury prediction model that incorporates clinical, Global-Positioning-System (GPS), and multiomics (genomics and metabolomics) data to better understand the factors associated with injury in elite female football players.